Comparative effectiveness of renin–angiotensin system inhibitors in hypertension - C Michael White (Journal of Comparative Effectiveness Research, 2012)
Evaluation of: Powers BJ, Coeytaux RR, Dolor RJ et al. Updated report on comparative effectiveness of ACE inhibitors, ARBs, and direct renin inhibitors for patients with essential hypertension: much more data, little new information. J. Gen. Intern. Med. doi:10.1007/s11606-011-1938-8 (2012) (Epub ahead of print). Hypertension is a chronic problem in the USA and there are three main ways to block the renin–angiotensin system: direct renin inhibitors, angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs). This article is a summary of a direct comparative effectiveness review of direct comparative trials in patients with hypertension. In patients with hypertension, ACEIs and ARBs provide similar blood pressure effects and no differences were seen in final health outcomes. ARBs have less ACE-induced cough and fewer withdrawals due to adverse events. Direct renin inhibitors versus ACE inhibitors or ARBs have not been extensively studied and their role is less clear.